2016
DOI: 10.1088/1538-3873/128/960/025001
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Contrast Ratio Imaging of Sirius with a Charge Injection Device

Abstract: The next fundamental steps forward in understanding our place in the universe could be a result of advances in extreme contrast ratio (ECR) imaging and point spread function (PSF) suppression. For example, blinded by quasar light we have yet to fully understand the processes of galaxy and star formation and evolution, and there is an ongoing race to obtain a direct image of an exoearth lost in the glare of its host star. To fully explore the features of these systems we must perform observations in which contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…GJ504 and κAnd are recent examples of young field stars with faint companions that were initially thought to have planetary masses (Carson et al 2013;Kuzuhara et al 2013) but which follow-up studies showed are probably older (Hinkley et al 2013;Bonnefoy et al 2014a;Fuhrmann & Chini 2015;Jones et al 2016), implying the companions are likely more massive and reside in the brown dwarf regime. Sirius is another example of a young massive field star extensively targeted with high-contrast imaging (Kuchner & Brown 2000;Bonnet-Bidaud & Pantin 2008;Skemer & Close 2011;Thalmann et al 2011;Vigan et al 2015;Batcheldor et al 2016). This system is particularly noteworthy for possible periodic astrometric perturbations to the orbit of its white dwarf companion Sirius B that may be caused by an still-hidden giant planet or brown dwarf (Benest & Duvent 1995).…”
Section: Field Stars and Radial Velocity Trendsmentioning
confidence: 99%
“…GJ504 and κAnd are recent examples of young field stars with faint companions that were initially thought to have planetary masses (Carson et al 2013;Kuzuhara et al 2013) but which follow-up studies showed are probably older (Hinkley et al 2013;Bonnefoy et al 2014a;Fuhrmann & Chini 2015;Jones et al 2016), implying the companions are likely more massive and reside in the brown dwarf regime. Sirius is another example of a young massive field star extensively targeted with high-contrast imaging (Kuchner & Brown 2000;Bonnet-Bidaud & Pantin 2008;Skemer & Close 2011;Thalmann et al 2011;Vigan et al 2015;Batcheldor et al 2016). This system is particularly noteworthy for possible periodic astrometric perturbations to the orbit of its white dwarf companion Sirius B that may be caused by an still-hidden giant planet or brown dwarf (Benest & Duvent 1995).…”
Section: Field Stars and Radial Velocity Trendsmentioning
confidence: 99%
“…Ninkov et al (1994) initially demonstrated the viability of CIDs for astronomical imaging. Batcheldor et al (2016) furthered these observations with a CID820. The CID820 used was a 2048×2048 12 μmpixel detector with linear response up to 268k e − and a full well of 305k e − .…”
Section: Charge Injection Devicesmentioning
confidence: 82%
“…This is one reason why CCDs were originally the preferred devices for astronomical applications. However, modern CIDs produce read noise levels comparable to CCDs because they include a pre-amplifier per pixel architecture, random access decoders, and a non-destructive read out (NDRO) approach (Eid 1995;Kimble et al 1995;Batcheldor et al 2016).…”
Section: Charge Injection Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary obstacle, however, is that the small orbital radius of the planet, which increases the contrast as seen above, also leads to an angular separation between the planet and star that is lower than the inner working angle of current coronographs and starshades as well as charge injection devices (Batcheldor et al 2016). Finally, we wish to highlight some other crucial issues that merit further study.…”
Section: Discussionmentioning
confidence: 99%